1989
DOI: 10.1093/ajcn/49.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, tooth eruption, and dental caries: a review

Abstract: Animal studies have shown that early malnutrition affects tooth structure, delays tooth eruption, and results in increased dental caries. However, epidemiologic evidence in support of these findings has been elusive. Cross-sectional surveys show that populations with a higher prevalence of caries in their deciduous teeth also show a lower prevalence of caries in their permanent teeth. However, longitudinal data from individuals show exactly the opposite. Caries development is also delayed as a consequence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
8

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 64 publications
2
40
0
8
Order By: Relevance
“…A similar longitudinal study suggested a cause-effect relationship between early malnutrition and increased dental caries [20]. Various studies in India also reported a significant association between a poor nutritional status and a delayed tooth eruption [21]. It can be concluded on the basis of these studies, that malnutrition caused delayed tooth development, it affected the age distribution of dental caries, and it resulted in an increased caries experience.…”
Section: Discussionmentioning
confidence: 88%
“…A similar longitudinal study suggested a cause-effect relationship between early malnutrition and increased dental caries [20]. Various studies in India also reported a significant association between a poor nutritional status and a delayed tooth eruption [21]. It can be concluded on the basis of these studies, that malnutrition caused delayed tooth development, it affected the age distribution of dental caries, and it resulted in an increased caries experience.…”
Section: Discussionmentioning
confidence: 88%
“…It is possible that such underlying health issues, related to socioeconomic factors, had also influenced the risk of developing tooth decay in the inmates from the Kilkenny Union Workhouse long before the Famine. While several clinical studies have reported a positive correlation between malnutrition and caries in primary teeth (Alvarez & Navia, 1989; Ismail, 1998; Johansson, Saellström, Rajan, & Parameswaran, 1992), there is currently a limited understanding as to whether the same relationship exists for the permanent dentition. A review article published in 2005 (Psoter, Reid, & Katz, 2005) only identified one longitudinal case study from Peru (Alvarez et al, 1993), where a link between early childhood protein‐energy malnutrition (PEM) and caries in the permanent dentition was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, when developing countries are exposed to sugars in the diet, the level of caries is greater than expected from experience in Western countries. This observation has led to the suggestion that malnutrition enhances the cariogenic effect of sugars (Enwonwu, 1973;Nikiforuk & Frazer, 1981;Alvarez & Navia, 1989).…”
Section: A L N U T R I T I O N a N D D E N T A L C A R I E Smentioning
confidence: 99%